Bridging experience, action, and culture in music education - Westerlund, Heidi (Sibelius-Akatemia, 2003)
This dissertation examines two contemporary theories of music education within a pragmatist frame of reference. By using methods of analysis and synthesis it shows how Bennett Reimer's and David J. Elliott's philosophies of music education manifest individualism and thus undermine the actual social context of music education. Predominantly through the use of John Dewey's philosophical tools, the work searches for a perspectival and holistic orientation in which music is understood as an embodied situational experience and learning as a process in and through social contexts. The study illustrates the continuity between the Cartesian-Kantian self, aesthetics and Reimer's theory. It points out that the dualistic isolation of the subject from the object, the mind from the body, and the individual from the social and communal is a shared tendency. Through its historical perspective, and by making a comparison to the traditional African conception of the self and its musical manifestations, the work argues that Reimer's theory is ethnocentric, and hence, narrows rather than widens the transformative possibilities of music as experience in education. It also shows how Reimer's notion of aesthetic experience is incompatible with his use of Dewey's holistic ideas. Elliott's Aristotelian praxis theory of music education tries to overcome the Cartesian "errors" by abandoning the notion of aesthetic experience in favour of musical action and emphasising music as authentic rule-based cultural information. The study analyses how Elliott's cognitive theory seems to neglect the sensing and feeling body, the student's perspective, and the actual context of learning and thus the ethics of praxis. Moreover, this research shows how the aesthetic and performance-oriented praxialism that Elliott poses as being in opposition can be combined in a Deweyan music education. Finally, the work discusses how Dewey's pedagogical ideas together with his commitment to cultural plurality, can bring forth a more socially, communally concerned and context-sensitive music education than either the individualistic theories of Reimer or Elliott do. Themes such as the project approach, democratic learning community, "oeuvres", and framing musical events are discussed in the search for holistic view of music education.

Väitöskirja tarkastelee kahta musiikkikasvatuksen nykyteoriaa pragmatistisessa viitekehyksessä. Työ osoittaa analyyttisin ja synteettisin menetelmin, kuinka Bennett Reimerin ja David J. Elliottin musiikkikasvatusfilosofiat manifestoivat individualismia eivätkä kiinnitä riittävästi huomiota musiikkikasvatuksen sosiaaliseen kontekstiin. Pääasiassa John Deweyn filosofisiin välineisiin nojautuen työ rakentaa holistista viitekehystä, jossa musiikki on situationaalinen, ruumiillinen (embodied) kokemus, ja jossa oppiminen konstituoituu sosiaalisessa kontekstissa ja sen kautta. Työ tarkastelee karteesis-kantilaisen ihmiskäsityksen, estetiikan sekä Reimerin teorian välistä jatkumoa. Se osoittaa, että niillä on samanlainen dualistinen tendenssi erotella subjekti ja objekti, mieli ja ruumis, sekä yksilö ja sosiaalis-yhteisöllinen. Historiallisen näkökulman avulla ja traditionaaliseen afrikkalaiseen ihmiskäsitykseen ja sen musiikillisiin ilmenemismuotoihin vertaamalla työ argumentoi, että Reimerin teoria on etnosentrinen. Se pikemminkin kaventaa kuin laajentaa musiikin transformatiivisia mahdollisuuksia kasvatuksessa. Työ osoittaa myös, kuinka Reimerin käsitys esteettisestä kokemuksesta on yhteensopimaton hänen käyttämiensä Deweyn holististen ajatusten kanssa. Elliottin aristoteelinen praksiaalinen musiikkikasvatusteoria yrittää välttää karteesiolaisuuden hylkäämällä esteettisen kokemuksen käsitteen, fokusoimalla musiikilliseen toimintaan ja tarkastelemalla musiikkia autenttisena, sääntöihin perustuvana kulttuurisena informaationa. Väitöskirja analysoi, kuinka Elliottin kognitiivinen teoria ei kuitenkaan riittävästi ota huomioon tuntevaa ja aistivaa kehoa, oppilaan näkökulmaa ja aktuaalista oppimiskontekstia ja näin ollen praksiksen etiikkaa. Tutkimus osoittaa myös, kuinka deweyläinen musiikkikasvatus voi yhdistää esteettisen käsitteen ja esittämis-painottuneen praksialismin, jotka Elliottin mukaan ovat yhteensopimattomia. Lopuksi työ pohtii, kuinka Deweyn pedagogiset sekä kulttuurisen pluralismin ajatukset voivat luoda vahvemmin sosiaalisesti ja yhteisöllisesti suuntautuneen, konteksti-sensitiivisemmän musiikkikasvatuksen kuin Reimerin tai Elliottin yksilökeskeiset teoriat. Projektilähestymistavan, demokraattisen ja oppivan yhteisön, yhteistaideteoksen ja musiikillisen tapahtuman "kehystämisen" teemojen kautta väitöskirja etsii holistisempaa lähestymistapaa musiikkikasvatukseen.
Keywords: Reimer, Bennett.; Elliott, David James.; Dewey, John.; musiikkikasvatus; filosofia; fi=musiikkikasvatus|sv=musikpedagogik|en=Music Education|